Assessing the Link between Community Engagement and Environmental Health Program Outcomes in Rural Indonesia - Mujtahidah (Asian Journal of Environmental Research, 2025)
Environmental health issues remain a major public health concern in rural Indonesia, where inadequate sanitation and waste management contribute to the persistence of preventable diseases. Community engagement in environmental health education is widely recognized as a key factor in enhancing program outcomes. This study aimed to assess the link between community engagement in environmental health education and the effectiveness of environmental health programs in rural Indonesia. A quantitative cross-sectional design was employed involving 467 respondents aged 17–74 years, with educational backgrounds ranging from no formal education to postgraduate levels. Data were collected using structured questionnaires and analyzed through Chi-Square and correlation tests. The findings revealed a statistically significant association between participation in environmental health education and program effectiveness (p = 0.000). The correlation coefficient (r = 0.445) indicated a positive and moderately strong relationship, suggesting that higher levels of engagement were associated with improved environmental cleanliness and health behaviors. These results underscore that participatory education fosters knowledge acquisition, behavioral change, and collective responsibility among community members. Strengthening participatory approaches through collaboration between local health authorities, educators, and residents is recommended to achieve sustainable improvements in environmental health and community well-being